GAMBARAN STATUS GIZI PEMAIN FUTSAL U-18 ANGIN PUYUH CLUB - Zulyar Firdaus Fathurohman Ahmad; Wisnu R Nugraha; David Ramadhan A.P Yudhistira; Bayu Tri Prasetyo; Muhammad Akmal Subarjah; Wiyogo Dwi Septiaji; Habibi Hadi Wijaya; Iha Nursolihah; Maha Dewi Affifah (Sports Collaboration Journal, 2024)
Nutritional status is one of the common indicators used to determine the balance of athlete intake. The realization of a person's potential and maximum achievement as an athlete is greatly influenced by optimal nutritional conditions. The purpose of this study was to determine the nutritional status of Angin Puyuh Club futsal athletes. This study is a quantitative descriptive study with a cross-sectional approach. The sample of this study was 30 people using the total sampling method. The instruments used included a weighing scale to weigh weight, a microtoice to measure height, and the BMI formula to calculate the nutritional status of athletes. The data obtained were analyzed descriptively using SPSS. The results of this study included 16 (53.3%) having normal nutritional status, 8 (26.7%) overweight, and 6 (20%) with underweight dietary status. This study concludes that there are still athletes with abnormal nutritional status (underweight and overweight) as many as 46.6%. Abstrak Status gizi merupakan salah satu indikator umum yang digunakan untuk mengetahui keseimbangan asupan atlet. Terwujudnya potensi dan prestasi maksimal seseorang sebagai seorang atlet sangat dipengaruhi oleh keadaan gizi yang optimal. Tujuan penelitian ini adalah untuk mengetahui gambaran status gizi atlet futsal Angin Puyuh Club. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan pendekatan crossectional. Sampel penelitian ini berjumlah 30 orang dengan menggunakan metode purposive sampling. Instrumen yang digunakan antara lain timbangan berat badan untuk menimbang berat badan dan microtoice untuk mengukur tinggi badan serta rumus IMT untuk menghitung status gizi atlet. Data yang didapat dianalisis secara dekskriptif menggunakan SPSS. Hasil pada penelitian ini antara lain terdapat 16 (53,3%) memiliki status gizi normal, 8 (26,7%) overweight dan 6 (20%) dengan status gizi underweight. Kesimpulan dari penelitian ini adalah masih terdapat atlet dengan status gizi tidak normal (underweight dan overweight) sebanyak 46,6%.